Strategic Planning Model of Islamic Religious Higher Education (PTKI) in Indonesia - Agus Zaenul Fitri; Nasukah, Binti; Tayeb, Azmil (Jurnal Pendidikan Islam, 2019)
Strategic planning for higher education is vital because it becomes a reference in determining the direction of policy and organizational performance. To win the competition in gaining the market, strategic planning activities become the spearhead in determining the strategy to achieve the appropriate institutional goals. However, the implementation of strategic planning at Islamic Religious Higher Education (PTKI) is often constrained because of the lack of understanding of the importance of these theories, so the implementation of strategic planning is often only intended for administrative requirements. Amid this condition, there is a phenomenon where some PTKIs are developing rapidly and transforming to be more market-oriented and to win the competition. These PTKIs are UIN Maulana Malik Ibrahim Malang, UIN Syarif Hidayatullah, IAIN Tulungagung, Muhammadiyah University of Malang, and Malang Islamic University. They have succeeded in creating effective strategies in organizational development until now they can become modern institutions and develop into multi-level organizations. The purpose of this study is to explore the five PTKI strategy models in Indonesia at the corporate and business unit levels based on Fred R. David's corporate-level strategy models, and Porter's generic strategy model theory Data were collected by qualitative methods through observation, interview, and documentation techniques. The results showed that at the corporate level, Fred R. David's strategy models applied by PTKI were vertical integration strategy, intensive strategy, and diversification strategy. In the defensive strategy, what is more, applied is the retrenchment strategy choice. However, at the business unit level, Porter's well-implemented strategy models are the cost leadership strategy, differentiation strategy, and focus strategy. These results have implications for the selection of business strategy models to be used in either profit-oriented or non-profit strategic planning activities in PTKI.